Local government green space policy for social well-being in selected areas of Malaysia - Danjaji, Abdulrahman Sa'adu (2014)
Urban green space is a network of natural and semi-natural features in a harmonious order that enhances human well-being, increases ecosystem resilience, and contributes to biodiversity conservation. The decreasing urban green spaces in our present-day cities are recognised to be a source of dissatisfaction in urban life. This negative scenario has given rise to the subsequent deterioration of urban quality of live which has impact on the overall well-being of urban population. This research did a systematic study of local government green spaces policy for social wellbeing in selected areas of Malaysia. The specific objectives of the research were to analyse planning policy related to urban green space provision in Peninsular Malaysia and to determine urban green space impacts on social well-being in Putrajaya. The research used a mixed method research approach. A qualitative document analysis of five selected planning instruments which guide physical development in Peninsular Malaysia was conducted. In examining the policy documents, several variables namely open space, natural areas, green corridors, and conservation were used. Each policy documents was scored from one to three points for each variable. In analysing the result of qualitative document analysis, systematic policy analysis was conducted following the model developed by Weiner and Vinings, which indicates the need for the rigorous implementation of urban green space policies. The study found that the provision of corridor or urban trails was given the least priority by the policies, while the protection of natural areas was accorded greater emphasis. The provision of urban green spaces and conservation of flora and fauna were given equal consideration by the policies. The policies analysed were comprehensive in covering urban green space provision in Malaysia but the present supply of urban green space was below the policy requirement of providing two hectares of urban green open space to every one thousand urban residents in Peninsular Malaysia. A questionnaire survey was also conducted in four selected green open spaces in Putrajaya. The survey results were analysed using descriptive and inferential statistical analysis. The descriptive statistics explained the socio-demographic information of respondent, while Pearson moment correlation analysis was performed to show relationship and direction of relation between two variables. Linear regression analysis was also conducted to determine which of the variables of urban green space (quality, quantity, and accessibility) are predictors of health promotion and satisfaction resulted from visiting urban green spaces in Putrajaya. Similarly, in predicting well-being which resulted from visiting urban green spaces, health promotion and satisfaction are used as independent variables. The results found that, visitation of urban green spaces contributed significantly to improvement of human well-being. The findings of this work indicated that, accessibility to urban green spaces had no statistical significance towards health promotion in Putrajaya. However, accessibility had a unique contribution to the satisfaction of the visitors of urban green spaces in Putrajaya, which is the most unique contributor of human well-being. The findings of the policy analysis indicated a need for the provision of more urban green open spaces in the majority of urban areas analysed in Selangor state. The study concluded that good quality, sufficient quantity, and well accessible urban green spaces should be provided to the urban population as those places could help the well-being of urban residents. In addition to overcoming lack of urban green spaces, the existing policies should promote creation of green corridors which would add to accessibility of urban green spaces and aesthetic quality of urban built environment.